O papel dos mecanismos psicobiológicos de sociabilidade no comportamento moral - Silveira, Matheus de Mesquita (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation aims to present a “sentimentalist-evolutionist” view of moral behavior, in order to argue that the emotional bonds elicited by empathy constitute the ground of morality. The argument starts from the concept of morals adopted by Adriano Naves de Brito, from Ernst Tugendhat's work, for whom morality is a relation of reciprocal demands presents in small groups. My proposal is to extend this concept in order to include not only human beings, but also mammals with complex social lives. The investigation of the motivational foundation of morality will be done from the writings of David Hume, for whom emotions ultimately represent the bases that lean individuals to approve or censor actions. A dissertation with a naturalistic proposal needs compatibilize its theoretical base with central concepts of evolutionism. Therefore, the reading of these authors and the arguments developed in the course of this investigation will be rooted in central concepts of the evolutionist theory, as proposed by Charles Darwin. Considering the importance that emotions and empathy have in the metaethical discussions about moral behavior, it is necessary to explain them from a naturalistic conceptualization. The debate between social constructivism and evolutionist psychology is relevant to this question. I will use studies on the physiology of socially relevant emotions of guilt, shame and anger, in order to defend its biological bases. Considering that an effect does not have a different nature of its cause, to show that emotions are expressed and recognized innately is a strong argument in the defense of its natural origin. However, even if emotions are expressed and recognized innately, it is important that individuals do not be indifferent toward its manifestation. Mechanisms psychobiological of sociability consists in an ideal candidate to explain the emotional bond inherent to small groups and central to a morality, explained in natural bases and compatible with evolutionist’s theories. In case one can explain the elements of normative behaviors in the ways of a “sentimentalist-evolutionist” approach, then it will obtain a real advance in the wider project of naturalization of morality.
Keywords: Moralidade; Sentimentalismo; Evolucionismo; Sociabilidade; Lobos; Morality; Sentimentalism; Evolutionism; Sociability; Wolves; ACCNPQ::Ciências Humanas::Filosofia